English as a Lingua Franca in Wider Networking : Blogging Practices. - Vettorel, Paola (Developments in English as a Lingua Franca DELF., 2014)
In a constantly interconnected world communication takes place beyond territorial boundaries, in networks where English works as a lingua franca. The volume explores how ELF is employed in internationally-oriented personal blogs; findings show how bloggers deploy an array of resources to their expressive and interactional aims, combining global and local communicative practices. Implications of findings in ELF and ELT terms are also discussed.